Examen especial a la contribución especial de mejoras del Gad Municipal Del Cantón Guano Periodo 2020. - Mancero Rojas, Elizabeth Alexandra (2022)
The following investigative work was elaborated with the objective of developing an Examination to the Special Contribution of improvements of “GAD Municipal del Canton Guano” year 2020. The beginning of the investigation was started with the knowledge of the general aspects of the GADM of Guano Canton, proceeding to the approach of the problem in order to establish the objectives and theoretical framework, the compilation of information was developed with the application of an interview to the directors of the areas involved in the determination of special contribution of improvements and surveys applied to the contributing inhabitants of Guano Canton, the development of the investigation was carried out through audit programs such as planning, execution and communication of results, with these programs proceeded with the verification and compliance with legal regulations, and continued with the administrative and financial management process through the determination, issuance, collection and registration of the special contribution for improvements for the 2020 period. The discoveries found in this research work are: the staff in charge of the special contribution of improvements is not trained and the inhabitants who contribute are not aware of this, for this reason the taxes are not totally paid, in addition, the ordinance is not applied as dictated by law, considering that, they are subjected to a resolution issued by directors, achieving evidence of accumulated overdue portfolio values.